Multicultural Education on Traditional Javanese Clothing in the Special Region of Yogyakarta - Lukmanul Hakim, Alif (Annpublisher, 2024)
Indonesia is one of the largest multicultural countries in the world. It is characterized by the many islands, tribes, languages, and religions in Indonesia. Of the many islands, tribes, languages, and religions, we need to preserve the culture in them. In preserving culture, one of them uses traditional clothing on several specified days so that the culture in our country is not lost and erased by the times. This study uses qualitative library research methods. The results of this research are in the form of data from various sources, such as reviewing books, journals, or other sources related to multicultural education and traditional Javanese clothing in Yogyakarta. In this case, the primary reference is the regulation of the governor of the Special Region of Yogyakarta, number 13 of 2023, concerning school uniform clothing for secondary and special education students and several sources related to multicultural education. The results of this study illustrate that multicultural education and culture have similarities in terms of culture, and also because when viewed from the determination that has been implemented by the governor of the Special Region of Yogyakarta, in this case, Sri Sultan Hamengkubuwono X. The purpose of the determination of the use of traditional Javanese clothing in Yogyakarta is to introduce Yogyakarta culture, especially to students and generally to the broader community.